Analysis of Bending Methods on BjTP 280 Roundbars on Hardness and Microstructure - Muttaqin, Adzin Hanif; Munir, Mohammad Miftachul; Rohmat, Imam Khoirul (Politeknik Negeri Lhokseumawe, 2023)
Reinforcing steel or commonly called roundbars is a material that is often used in industry, this is because the material is strong and easy to find anywhere. Deformation has a relationship to hardness. The higher the deformation value, the higher the material hardness value, but this is inversely proportional to the grain change, where the greater the deformation, the smaller the grain size. This research aims to determine the hardness and microstructure values of cold bending and hot bending treatments. Research by carrying out cold bending and hot bending which is connected to roundbars material without BjTP 280 bending treatment with the SMAW welding process. The highest hardness value is shown in the HAZ area of the hot bending specimen with a hardness value of 239.97 HV with a fine and small microstructure so it has the highest hardness value.